The Presence of Masculinity on the Prince Characters in Fairytale: Rapunzel by The Brothers Grimm - Eva Fatimah (Dinamika Bahasa dan Budaya, 2021)
Abstract The discussion of masculinity in literary studies is still relatively needed as a research topic. Masculinity is a theory of action or work in everyday social life. This view appears as hegemony in society on how men should act and respond to ideas or problems. This construction is often found in love stories where the male character acts like someone who is admired or called a heroine. The genre of romance is often found in a fairytale which usually has male and female characters. Although the main character is a female, the stereotype of the fairy tale itself favors the male character. This is considered disguised masculinity yet many people unaware. The research uses masculinity as a topic and theory in the story of Rapunzel by the Brothers Grimm, and also uses a genetic structuralism approach by Lucien Goldmann. This approach is suitable because it combines the structure into a whole in the data and relates it to the social conditions that underlie the creation of the work. Keywords: Masculinity, Fairytale, Male, Rapunzel, Brothers Grimm, Genetic Structuralism, Lucien Goldmann.